2021
DOI: 10.1155/2021/8857572
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Knowledge Management and Its Effect on Organizational Performance: Mediating the Role of Human Capital

Abstract: This study aims to investigate and identify the factors affecting the empowerment and implementation of knowledge management in organizations as well as the impact of knowledge management on organizational performance. This study also examines the mediating role of human capital in the relationship between knowledge management and performance of Kabul Steel Plant, which is the largest steel plant in Afghanistan. The research model was developed through the literature review. The initial data were collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 61 publications
(87 reference statements)
6
61
0
Order By: Relevance
“…In addition to the direct relationship between talent management and performance, Alqershi et al (2019) emphasized that scholars have shown an interest in the mediating role of human capital (Rezaei et al, 2021;Subramony et al, 2018;Nieves and Quintana, 2018). We provide confirmatory evidence for the mediating effect of human capital in the relationship between TMM and SBP, which means that H6 is supported.…”
Section: Effect Of Talent Managementsupporting
confidence: 63%
“…In addition to the direct relationship between talent management and performance, Alqershi et al (2019) emphasized that scholars have shown an interest in the mediating role of human capital (Rezaei et al, 2021;Subramony et al, 2018;Nieves and Quintana, 2018). We provide confirmatory evidence for the mediating effect of human capital in the relationship between TMM and SBP, which means that H6 is supported.…”
Section: Effect Of Talent Managementsupporting
confidence: 63%
“…Individuals have a wide variety of experiences, beliefs, aspirations, and problem-solving approaches (Khan Et Al., 2020). Therefore, Psychological capital is introduced as a mediating variable to investigate the effect of strong predictors on project performance (Rezaei et al, 2021). Psychological capital is a collection of assets that can be used to help the person improve their job performance and achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Education level helps to determine a person's ability to absorb and understand science (Notoatmodjo 2010). There are external factors that can affect a person's knowledge, namely education, mass media exposure, economic, social relationships and experience (He et al 2016, Rezaei et al 2021.…”
Section: Discussionmentioning
confidence: 99%